We Wish You Luck - Zancan, Caroline (New York : Riverhead Books, 2020)
"A coming-of-age campus novel about a group of students who take revenge on a professor after she destroys one of their own. It doesn't take long for the students on Fielding campus to become obsessed with Hannah, Leslie and Jimmy. The three graduate students are mysterious, inaccessible, and brilliant. Leslie, glamorous and brash, has declared that she wants to write erotica and make millions. Hannah is quietly confident, loyal, elegantly beautiful, and the person they all want to be; and Jimmy is a haunted genius with no past. After Simone - young, bestselling author and erstwhile model - shows up as a visiting professor, and after everything that happened with her, the trio only become more notorious. Love. Death. Revenge. These age-old tropes come to life as the semesters unfold. The threesome came to study writing, to be writers, and this is the story they've woven together: of friendship and passion, of competition and envy, of creativity as life and death. Now, they submit this story, We Wish You Luck, for your reading pleasure" -- Provided by publisher.
Keywords: Revenge -- Fiction; College students -- Fiction; Authors -- Fiction; Campus fiction